Refounding political governance : the metaphysics of public administration - Cutting, Bruce; Kouzmin, Alexander (Public policy, administration and management., 2011)
Re-founding Political Governance: The Metaphysics of Public Administration points to a possible paradigm shift in the way Anglo-American Public Administration should be understood and analyzed. The book presents a unique approach to the analysis of power, leadership and management in Public Administration. The central theme is that humans make organizations in their own image and these organizations, in turn, are a product of the way humans think and act. The book extrapolates from historical philosophy and personality typologies to explain the dynamics and evolution of Public Administration. With the philosophical framework and approach clearly explained, the book provides a critique of current practice and recommends what is required to re-invent Public Administration, rather than New Public Management, in Anglo-American contexts. The book explains a new, more complex, and more useful, understanding of the dynamics of contemporary US Public Administration situated within the American Constitution. This book is ground-breaking and should be useful in all graduate Public Administration courses and professionals in the field of Public Administration.